2022
DOI: 10.1128/jcm.02262-21
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Antigen SARS-CoV-2 Serological Assay Reflects Antibody Avidity

Abstract: Serial antibody measurements using an array of SARS-CoV-2 immunoassays have demonstrated differing kinetics among assay platforms (1).…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…The third limitation is that the anti-S antibody data were capped at 2500 IU/mL because of the relative lack of linearity of the used technique above this level. The use of a double antigen-sandwich method (Roche Elecsys immunoassays) could also be a limitation since a recent study showed that the avidity of the SARS-CoV-2 antibodies could affect the results with this type of assay [ 37 ]. Another limitation is the small number of subjects in which cellular immune response was studied.…”
Section: Discussionmentioning
confidence: 99%
“…The third limitation is that the anti-S antibody data were capped at 2500 IU/mL because of the relative lack of linearity of the used technique above this level. The use of a double antigen-sandwich method (Roche Elecsys immunoassays) could also be a limitation since a recent study showed that the avidity of the SARS-CoV-2 antibodies could affect the results with this type of assay [ 37 ]. Another limitation is the small number of subjects in which cellular immune response was studied.…”
Section: Discussionmentioning
confidence: 99%
“…The time interval and the administration of additional doses of vaccine enhances the maturity of elicited antibodies and increases their avidity toward targeting antigens [30] . The Elecsys platform is more likely to detect antibodies with higher avidity [31] . In SARS-CoV-2-naïve individuals, a single dose of mRNA vaccine generates antibodies of incomplete maturity, and high-affinity antibodies are only elicited after the second dose [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Nakagama et al [ 23 ] followed the convalescent phase of patients with COVID-19, measuring anti-RBD antibody titers using Elecsys ® Anti-SARS-CoV-2S (anti-RBD total Ig; Roche) and ARCHITECT SARS-CoV-2 IgG II Quantitative (Abbott) and indicated that the antibody titers measured by the Roche system were high avidity indices, and persisted even in the late convalescent period. Matusali et al [ 24 ] investigated the dynamic association among binding and functional antibodies in healthcare workers receiving the BNT162b2 mRNA COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%